The association between alteration of maternal lipid levels and birthweight at term: A within-family comparison - Chen, Qinqing; Chen, Huiqi; Wang, Minmin; Qiu, Liping; Xi, Fangfang; Jiang, Ying; Lv, Min; Huang, He-Feng; Luo, Qiong (Frontiers in Endocrinology, 2022)
Context: Maternal lipid levels affects birthweight and the long-term health of the offsprings. However, this relationship could be confounded by genetic and other shared effects. Objective: This work was aimed to examine the association between maternal lipid levels and birthweight using population-based data that allowed us to compare two pregnancies in the same mother. Methods: In this population-based cohort study, 705 women and their 1 410 offsprings were included. From an initial sample of women with more than one singleton birth in the database, we made the following exclusions: missing data for pre-pregnancy BMI, pregnancy weight gain, birthweight and lipid values; maternal age less than 19 years old or older than 44; gestatioal age less than 37 weeks or more than 41weeks. Serum samples were collected during second and third trimesters for evaluation on fasting total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels. Then we assessed the association between maternal lipids and birthweight. Results: Infants of women whose 2nd-trimester TG increased by 10th-20th percentile (-0.93~-0.59 mmol/L) from 1st to 2nd pregnancy were 191.750g (8.112~ 375.388) lighter at birth than were infants of women those of 40th-50th percentile (-0.20~-0.03 mmol/L). Parity, gestational age, neonatal gender, maternal pre-pregnancy body mass index (BMI), maternal weight gain, and 3rd-trimester TG were all associated with higher birth weight. Every unit increase in TG in the third trimester increases birthweight by 49.12g. Conclusion: Maternal TG level is associated with birthweight independent of shared genes. TG may be used to predict birthweight.